2001
DOI: 10.1080/09658210143000038
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of errors in short-term forgetting in AD and ageing

Abstract: This study examined whether the low performance of 40 AD patients in the Brown-Peterson task could be explained by a pattern of errors that differed from 55 elderly controls. Our quantitative results showed that AD patients had a lower performance level in the three retention intervals than controls but a significant interaction between group and interval was not found, indicating that the rate of forgetfulness was similar in the two groups. In our qualitative analysis, errors were categorised as confusions, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Regarding digit span, while some authors have not found any significant differences between AD patients and controls [5,7], others have recorded impaired performance in AD patients [3,8,18,34,41,50]. The dis- Table 2 caption for abbreviations a this cluster includes superior frontal areas, the caudate nuclei, the anterior and the middle cingulate gyri, the precentral gyrus and the thalamus Table 3 Peak coordinates of the significant correlations between cerebral glucose metabolism and verbal working memory performance (digit span and BPP-6) in late and early onset AD groups, controlling for age effects crepancies between these findings may be due to a failure to take age at onset into account.…”
Section: Discussionmentioning
confidence: 95%
“…Regarding digit span, while some authors have not found any significant differences between AD patients and controls [5,7], others have recorded impaired performance in AD patients [3,8,18,34,41,50]. The dis- Table 2 caption for abbreviations a this cluster includes superior frontal areas, the caudate nuclei, the anterior and the middle cingulate gyri, the precentral gyrus and the thalamus Table 3 Peak coordinates of the significant correlations between cerebral glucose metabolism and verbal working memory performance (digit span and BPP-6) in late and early onset AD groups, controlling for age effects crepancies between these findings may be due to a failure to take age at onset into account.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, AD patients presented specific difficulties in comparison to normal elderly subjects in recalling information, in the sense that they produced more intrusions of the TBF trigrams, and that these errors were not explained by span size or speed of processing. It has frequently been reported that AD patients produce more intrusions [2,12,19,69] and perseveration errors [41,42,91] during word recall tasks. Thus, we can suggest that, unlike normal elderly subjects who only have difficulties completely suppressing TBF items from working memory but clearly distinguish between TBF and TBR items (since they produced no more intrusions than young subjects), AD patients have additional difficulties inhibiting the production of the TBF items.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to semantic inhibition, Collette et al [23] observed a weaker ability to suppress semantically related but task-irrelevant responses on the Hayling task [17], 5 and Duchek et al [36] found that AD patients are disproportionately influenced by semantically related distracting information during a reading task. Finally, perseverations [41,42,91] and intrusion errors [2,12,19,69] are frequently produced by AD patients during list recall performance, indicating an impairment of the suppression processes associated with explicit memory tasks.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the present work focuses on the location modelling and prediction. Easy procedures are proposed to interpret surveillance at home data and to provide a perseveration index which may used to trigger alarms and counselling diagnosis search for cognition impairment (Miyoshi 2009, Joray et al 2004, Sebastian et al 2001. To reduce the complexity of the problem, a preliminary hypothesis is adopted.…”
Section: The His and Ailisa Experimental Platformsmentioning
confidence: 99%